Studies on the flora of the North Blosseville Kyst and on the hot springs of Greenland. - Halliday, G.; Kliim-Nielsen, L.; Smart, I. H. (Meddelelser om Grønland, 1974)
The vascular plants and bryophytes found by recent expeditions to the north Blosseville Kyst, East Greenland, are recorded. Four species, all occurring by the hot springs in Knighton Fjord (69°22' N. !at., 24°43' W. long.), are new to the flora of Greenland: Archidium alternifolium (HEDW.} MITT., Fossombronia wondraczekii (CORDA) DUM., Ophioglossum azoricum C. PRESL and Geum rivale L. Several species found at these springs and also at those in R0mer Fjord here reach their northern limits in East Greenland. The vegetation around these hot springs and at -Onartoq, in South Greenland, is described. All the known hot springs in Greenland are mapped and data, where available, are given on their temperatures and physical and chemical characteristics. The four species new to Greenland all occur in Iceland and the hypothesis of dispersal by migrating wildfowl is regarded as very plausible.